Effect of Cadmium on Lipid Peroxidation and Activities of Antioxidant Enzymes in’ Moth Bean Callus - Bora, K K; Mathur, Sudha R; Ganesh, R (Annals of Arid Zone, 2016)
Effect of cadmium on lipid peroxidation and some antioxidant enzymes was studied in callus of moth bean after 7. ]4 and 21 days of cadmium nitrate (Cd(N03)2) addition to culture medium. Cd enhanced malondialdehyde (MDA) content in moth bean callus indicating enhanced lipid peroxidation. Superoxide dismutase (SOD) activity also significantly increased following cadmium addition in culture medium. ]n contrast, activities of catalase (CAT), peroxidase (PO). polyphenoloxidase (PPO), ascorbate peroxidase(APX) and acid phosphatase (acid-P) were significantly reduced. Results suggest that Cd induced oxidation injury in moth bean callus is caused by enhancing lipid peroxidation and inhibiting activities of some enzymes viz .. CAT, PO and APX of antioxidant defense mechanism. Enhanced SOD activity indicates that the enzyme served as important component of defense mechanism against metal-induced oxidation injury.